The Impacts of Migration and Remittances on Agricultural Labour: Evidence from Karnataka State in India - Venu B. N.; Navya A. G.; Babu, Suresh; Mopuri, Ramgopal (Contemporary Research in Business, Management and Economics Vol. 4, 2024)
Indian agriculture was marked by a plentiful supply of farm labour till recent years. The Migration is a major option of agricultural labours in rainfed regions of Karnataka for their better livelihood. The purpose of this study is to analyse the migration of agricultural labour in Karnataka. Most of the labours migrate from rainfed to irrigated regions of Karnataka. However, the younger generation in rural areas is increasingly migrating to non-farm sector. Remittances have a major impact on the welfare of recipient households and the main source of income for labour households in the study areas. Remittances were spent on food, education, health and consumer goods. The total sample for the study comprised 120 agricultural labour households. The primary data required for the study was collected from the randomly selected agricultural labour households through personal interviews using a pre-tested structured schedule. The study revealed that, most of the labourers in irrigated situation migrated near village and within the district but in rainfed situation, labour migration to other districts was relatively high. In both the situation majority of labourers migrated seasonally and the frequency was highest (7 0%) in rainfed situation. In rainfed situation, after sowing season they were migrated to other regions and return at the time of harvest.